Media Pembelajaran Mistery Box: Peningkatan Perilaku Hidup Bersih dan Sehat (PHBS) Anak Usia Dini - Feny Kurnia; Mustika Dewi Muttaqien (STAI Al-Hamidiyah Jakarta, 2024)
This research based on the factors of low clean and healthy living behavior in children and mystery box media plays a very important role in increasing clean and healthy living behavior in children. Because of the result of observations at PAUDQu Darul Falah Depok that there were 8 children who were still low in awareness of clean and healthy living behavior. The purpose of this study was to find out the application of the mystery box media and to find out the increase in clean and healthy behavior in children through mystery boxes. The subjects in this study were a group of students, with 8 students consisting of 4 boys and 4 girls. The object of this study is clean and healthy living behavior through the mystery box media. The method in this study uses the classroom action research method developed by Kemmis and McTaggart through four stages, namely planning, action, observation, and reflection. The flow of this research was carried out in two cycles. The result of this study is that children’s clean and healthy living behavior increases. This can be proven in the pre-cycle activities; the result was 44.78%. Continuing in the activities of cycle I meeting 1, the result was 49.9%. At meeting 2, the result was 52.59%. And at meeting 3, the result was 61.97%. Then in the activity cycle II meeting 1, the result was 67.81 %. At the second meeting, the result was 72.91%. And in the third meeting, the result was 80.20%. It can be concluded that the mystery box can improve clean and healthy living behavior in group A children at PAUDQu Darul Falah Depok.